Handling Guest Complaints Management of Selected Hotel in Quezon City: An Assessment: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Customer complaints will unavoidably occur, no matter how effective the business is. If there’san overlooked or dismissed complaint, it may seem to effectively tell the client that theircomments were not valued. Many business owners consider handling complaints to be a time-consuming and irritating process. However, by developing an efficient method, problems maybe resolved quickly and easily. Even though we are aware that Filipinos have highexpectations for services, it is vital to handle complaints that travelers lodge with hotels allover the Philippines. Particularly when their complaint was not promptly resolved. Typically,some visitors may complain about your hotel on social media. It is not desired. The hotel'sstaff, as well as guests, will be affected.This study reveals that amenities can also cause vexation of the guests while on theirpremises, and the absence of personalized services in the room services may cause irritationto the guests. The overall hotel management might have a lack of knowledge in terms ofoperation during the guests' stays. It can be the reason for the dissatisfaction of their guests.It is advised that the staff listen patiently, which is essential for effectively handling clientissues. The staff members should be respectful and truly respond by acknowledging thedifficulties raised by the guests, taking ownership of the situation, offering a solution,expressing their commitment to improving, requesting a second chance to do so, and acting ina professional manner on all platforms. In order to prevent mistakes when joining thehospitality sector, and especially the hotel industry, it is advised that the students be moreeducated about hotel services.
Keywords: Business